PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA PT. ANEKA BUMI PRATAMA (ABP ) KEC. PEMAYUNG - Ratna Ratna (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Effect of compensation and motivation to work performance at PT. ANEKA BUMI PRATAMA (ABP) In Simpang Kubu Kandang – Subdistrict Pemayung. The purposes of this paper are :1.   To determine the employee received compensation in PT. Aneka bumi pratama (ABP) at Simpang kubu kandang Subdistrict Pemayung.2.   To know the motivation of employees working at PT. Aneka bumi pratama (ABP) at Simpang kubukandang pemayung.3.   To determine the effect of compensation and motivation on employee performance at PT. Aneka bumi pratama (ABP) in the intersection kubukandang pemayung.Data collection methods used in the survey methods used to obtain information from respondents with interview techniques and disseminate how ticklish and using the measurement Likert Scale. populations in this study are all of employee at PT. Aneka bumi pratama (ABP) 865. Whereas for sample 120 employees. Data analysis tools in use linier regression multiple methods using SPSS program support computer.the results of the analysis that the compensation positive influence to motivation significant effect on employee at PT. Aneka bumi pratama (ABP).Keyword :  compensation, motivation, employee performance